Biologging Physiological and Ecological Responses to Climatic Variation: New Tools for the Climate Change Era - Chmura, Helen E.; Glass, Thomas W.; Williams, Cory T. (Frontiers in Ecology and Evolution, 2018)
In this mini-review, we discuss how biologging technology can be used to detect, understand, and forecast species’ responses to climate change. We review studies of phenology, thermal biology, and microhabitat selection as examples to illustrate the utility of a biologging approach in terrestrial and aquatic species. These examples show that biologgers can be used to identify and predict behavioral and physiological responses to climatic variation and directional climate change, as well as to extreme weather events. While there is still considerable debate as to whether phenotypic plasticity is sufficient to facilitate species’ responses to climate change or whether responses to short-term climate variability are predictive of climate change response, understanding the scope and nature of plasticity is an important step towards answering these questions. One advantage of the biologging approach is that it can facilitate the measurement of traits at the level of the individual, permitting research that investigates the degree to which physiology and behavior are plastic. As such, combining biologging with metrics of fitness can provide insight into how plasticity might confer population and species resilience to climate change. Increased use of biologgers in experimental manipulations will also yield important insight into how phenotypic flexibility allows some animals to mitigate the negative consequences of climate change. Although biologging studies to date have mostly functioned in measuring phenotypic responses to short-term climate variability, we argue that integrating biologging technology into long-term monitoring programs will be instrumental in documenting and understanding ecological responses to climate change.